Non-invasive Measurement of Pulmonary Gas Exchange Efficiency: The Oxygen Deficit - Prisk, G. Kim; West, John B. (Frontiers in Physiology, 2021)
The assessment of the efficiency of pulmonary gas exchange has long been assessed using the alveolar-arterial difference in PO2, the A-aDO2, a construct developed by Richard Riley ~70 years ago. However, this measurement is invasive (requiring an arterial blood sample), time consuming, expensive, uncomfortable for the patients, and as such not ideal for serial measurements. Recent advances in the technology now provide for portable and rapidly responding measurement of the PO2 and PCO2 in expired gas, which combined with the well-established measurement of arterial oxygen saturation via pulse oximetry (SpO2) make practical a non-invasive surrogate measurement of the A-aDO2, the oxygen deficit. The oxygen deficit is the difference between the end-tidal PO2 and the calculated arterial PO2 derived from the SpO2 and taking into account the PCO2, also measured from end-tidal gas. The oxygen deficit shares the underlying basis of the measurement of gas exchange efficiency that the A-aDO2 uses, and thus the two measurements are well-correlated (r2~0.72). Studies have shown that the new approach is sensitive and can detect the age-related decline in gas exchange efficiency associated with healthy aging. In patients with lung disease the oxygen deficit is greatly elevated compared to normal subjects. The portable and non-invasive nature of the approach suggests potential uses in first responders, in military applications, and in underserved areas. Further, the completely non-invasive and rapid nature of the measurement makes it ideally suited to serial measurements of acutely ill patients including those with COVID-19, allowing patients to be closely monitored if required.